Oregon Writes Open Writing Text - Kepka, Jenn; Open Textbook Library (Open Textbook Library, 2018)
This textbook guides students through rhetorical and assignment analysis, the writing process, researching, citing, rhetorical modes, and critical reading. Using accessible but rigorous readings by professionals throughout the college composition field, the Oregon Writes Writing Textbook aligns directly to the statewide writing outcomes for English Composition courses in Oregon.
Introduction -- Part 1: Situation and Analysis -- Part 2: The Writing Process -- Part 3: Research -- Part 4: Rhetorical Modes -- Part 5: Critical Reading
In English.
Description based on print resource
Keywords: Education -- Textbooks; Education, Higher -- Textbooks; Humanities -- Textbooks; Rhetoric -- Textbooks